Influence of Alternating Magnetic Field on Physical and Mechanical Properties of Crystals - Karas, V.I.; Karasyova, E.V.; Mats, A.V.; Sokolenko, V.I.; Vlasenko, A.M.; Zakharov, V.E. (Металлофизика и новейшие технологии, 2016)
The results of the investigation of creep characteristics and activation parameters of polycrystalline nickel (of 99.996% purity) plastic flow at the temperature of 77 K are presented. The influence of nonstationary magnetic field with strength of 500 Oe (harmonic (50 Hz) and monopolar pulses of the same frequency) on the nickel creep characteristics is studied. We have deliberately conducted experimental investigations of the influence of nonstationary magnetic field of alternating and constant sign at constant temperature in order to estimate the contribution to the dislocations’ mobility from the interaction of dislocations with the mobile domain boundaries as well as from the heat effects connected with the induction electric field. The proposed model of electroplastic effect (EPE) suggests the following mechanism of weakening under the action of electric field. Electric field gives energy to conductivity electron subsystem, making it thermodynamically nonequilibrium. Nonequilibrium electrons while interacting with acoustic phonons transfer more energy to short-wave part of the phonon spectrum. Short-wave phonons due to large stress gradient effectively detach dislocations from stoppers. Experimental results qualitatively match with the data obtained after numerical calculations.